Roots ancient or medieval? Nikolaos Politis, modern Greek folklore studies and ancient Greek religion - Marinis, Agis (The Historical Review/La Revue Historique, 2020)
The question posed by the title can be reformulated in the following manner: to what extent has it been possible or desirable to connect modern Greek customs with ancient ones? not customs in general, but more precisely religious customs. Greek folklore studies typically begin with Nikolaos Politis, professor at the University of Athens, the first to introduce the term λαογραφία (meaning “folklore studies”) towards the end of the nineteenth century. Yet, we need to revert to at least as far back as the time prior to the Greek Revolution, that is, the period of the Greek enlightenment, in order to trace the beginnings of the shaping of the ideological framework of modern Greek folklore studies. it is well known and has aptly been pointed out, also in connection with Greek folklore studies, that for the Greeks the enlightenment movement went hand in hand with a specific form of romanticism. The Greek idea of the nation developed within the framework of the Romantic movement and on the basis of the connection between “us” and “the ancients”. How, then, were modern Greek folk customs that were not firmly related to the orthodox church incorporated in this new cultural narrative?